Upaya Peningkatkan Pengetahuan Wanita Usia Subur tentang KB IUD - maiseptyasari, ruri (Poltekkes Kemenkes Bengkulu, 2023)
Intrauterine Contraception Device (IUD) is a method of contraception that is quite safe and is the most recommended in the national family planning program in Indonesia. compared to other methods of contraception such as injections, pills and implants. IUDs can prevent pregnancy for up to 10 years with a failure rate of only about 1%. Presentation on IUD use at the Padang Serai Health Center 5.9% of this activity will be carried out at several Posyandu in Padang Serai Health Center from May 3 to May 23 2023. The target of this activity is Women of Reproductive Age (WUS), totaling 167 people. The method of this activity is to distribute leaflets to participants then conduct counseling and evaluate using a pre-post test questionnaire. The results of the activity revealed an increase in mother's knowledge. The average knowledge of mothers about IUD family planning before counseling was 48% and increased to 83% after counseling. The service team recommends using IUD KB by paying attention to the many advantages it has.